2010
DOI: 10.12968/ijpn.2010.16.1.46180
|View full text |Cite
|
Sign up to set email alerts
|

A study of patients with a primary malignant brain tumour and their carers: symptoms and access to services

Abstract: Aim: To investigate the symptom experience, access to supportive care services and rehabilitation of patients with a primary malignant brain tumour (PMBT) and their carers. Methods: A case review of 70 patients with a diagnosis of PMBT who received palliative care in fi ve specialist palliative care units between July 2005 and June 2006. The review examined patients' symptom experience, care issues, access to rehabilitation and access to supportive care services. Results: The two most signifi cant issues exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 19 publications
6
55
0
1
Order By: Relevance
“…Our results add to growing evidence that a gap between patients' needs and their use of supports or support services exists [2][3][4][11][12][13]. The gap may be partly due to factors relating to the availability of appropriate services, particularly in regional or rural areas [14].…”
Section: Introductionsupporting
confidence: 57%
“…Our results add to growing evidence that a gap between patients' needs and their use of supports or support services exists [2][3][4][11][12][13]. The gap may be partly due to factors relating to the availability of appropriate services, particularly in regional or rural areas [14].…”
Section: Introductionsupporting
confidence: 57%
“…Other studies have reported that psycho-social needs are less likely to be triggers for referral to PC services, (12,33) that physicians' ratings of patient concur poorly with patients' ratings, (34) and that carers' needs are not routinely documented. (35) Problems also relate to insufficient trained staff with knowledge about referral to palliative care. (31) Late referrals may result in poorer transition between acute and palliative care services, indicated by lower satisfaction with care received and a higher number of unmet needs than those referred earlier.…”
Section: Patient and Family-related Issuesmentioning
confidence: 99%
“…Breast cancer (BC) is the most common malignancy in women [1], comprising up to 16% of all cancers in women [2]. Primary brain tumours (BT), a comparatively rare and diverse group of neoplasms, account for 2% of all cancers [3] and affect 7 per 100,000 population annually worldwide [4]. The overall incidence of BC and BT is on increase worldwide [2].…”
Section: Introductionmentioning
confidence: 99%